The relative contribution of antibodies, CD4+ and CD8+ T cells to sporozoite-induced protection against malaria. - Rodrigues, M (1993)
Protective immunity against Plasmodium yoelii, induced by sporozoite immunization, was investigated using a quantitative method based on the measurement of plasmodial ribosomal RNA in the liver of sporozoite-challenged mice. The relative importance of the different immune mechanisms induced by sporozoite immunization was determined by evaluating quantitatively the anti-parasite activity of antibodies, CD4+ and CD8+ T cells. The role of antibodies was determined by passive transfer of immune sera to naive mice. The transfer to mice of sera obtained after a single immunizing dose reduced the liver stages by 47%. The respective contribution of CD4+ and CD8+ T-cell subsets was determined in B10 (H-2b) mice, treated with a monoclonal antibody (mAb) which inhibits B-cell maturation, and subsequently immunized once with irradiated sporozoites. These mice produced low levels of anti-sporozoite antibodies, but were capable of inhibiting the development of liver stages as efficiently as non-manipulated immunized mice. Administration of either anti-CD4 or anti-CD8 mAb to these mice, did not significantly decrease their capacity to inhibit the development of liver stages. We only observed a significant loss of immunity when the mice were depleted in vivo of both CD4+ and CD8+ T cells. In contrast to earlier studies, we found that the induction of protective immunity is not a phenomenon restricted to a few strains of mice having a particular genetic make-up. The apparent non-responsiveness observed in some strains of mice can be overcome by using larger immunizing doses.